Pharmacokinetics and in vitro/in vivo antitumor efficacy of aptamer-targeted Ecoflex® nanoparticles for docetaxel delivery in ovarian cancer - Ghassami E (Dove Medical Press, 2018)
Erfaneh Ghassami,1 Jaleh Varshosaz,1 Ali Jahanian-Najafabadi,2 Mohsen Minaiyan,3 Parvin Rajabi,4 Effat Hayati5 1Department of Pharmaceutics, School of Pharmacy and Novel Drug Delivery Systems Research Centre, 2Department of Pharmaceutical Biotechnology, 3Department of Pharmacology, School of Pharmacy, 4Department of Pathology, Isfahan University of Medical Sciences, Isfahan, 5North Research Center, Pasteur Institute of Iran, Amol, Iran Purpose: Epithelial ovarian cancer is the fourth cause of cancer death in developed countries with 77% of ovarian cancer cases diagnosed with regional or distant metastasis, with poor survival rates. Docetaxel (DTX) is a well-known anticancer agent, with clinically proven efficacy in several malignancies, including ovarian cancer. However, the adverse effects caused by the active ingredient or currently marketed formulations could even deprive the patient of the advantages of treatment. Therefore, in the current study, polymeric nanoparticles (NPs) equipped with aptamer molecules as targeting agents were proposed to minimize the adverse effects and enhance the antitumor efficacy through directing the drug cargo toward its site of action.Materials and methods: Electrospraying technique was implemented to fabricate poly (butylene adipate-co-butylene terephthalate) (Ecoflex®) NPs loaded with DTX (DTX-NPs). Afterward, aptamer molecules were added to the DTX-NPs, which bound via covalent bonds (Apt-DTX-NPs). The particle size, size distribution, zeta potential, entrapment efficiency, and release profile of the NPs were characterized. Using MTT assay and flow-cytometry analysis, the in vitro cytotoxicity and cellular uptake of the NPs were compared to those of the free drug. Following intravenous administration of Taxotere®, DTX-NPs, and Apt-DTX-NPs (at an equivalent dose of 5 mg/kg of DTX), pharmacokinetic parameters and antitumor efficacy were compared in female Balb/c and HER-2-overexpressing tumor-bearing B6 athymic mice, respectively.Results: The obtained results demonstrated significantly enhanced in vitro cytotoxicity and cellular uptake of Apt-DTX-NPs in a HER-2-overexpressing cell line, comparing to DTX-NPs and the free drug. The results of in vivo studies indicated significant increment in pharmacokinetic parameters including the area under the plasma concentration–time curve, mean residence time, and elimination half-life. Significant increment in antitumor efficacy was also observed, probably due to the targeted delivery of DTX to the tumor site and enhanced cellular uptake as evaluated in the aforementioned tests.Conclusion: Hence, the proposed drug delivery system could be considered as an appropriate potential substitute for currently marketed DTX formulations. Keywords: Ecoflex, nanoparticles, aptamer, electrospraying, pharmacokinetic, ovarian cancer, docetaxel